Mapping crop and livestock value chain actors in Mbire and Murehwa districts in Zimbabwe - Ngoma, Hambulo; Matangi, Dorcas; Zingwena, Taurai; Debello, Moti Jaleta; Baudron, Frederic (CGIAR, 2023)
We conducted a preliminary value chain actors mapping for major crops grown and livestock kept by smallholder farmers in Mbire and Murehwa districts of Zimbabwe. Accordingly, in this report we mapped value chain actors for 11 crops and livestock commodities: namely, sorghum, cotton, sesame, maize, groundnut, sweet-potato, vegetables (tomato and onion), cattle, goats, poultry, and honey/beekeeping. Except sesame from Mbire, most of the crop and livestock commodities are channeled to the main markets in Harare and Marondera for Murehwa. Sesame is smuggled to Mozambique and the market is mainly dependent on middlemen. The Grain Market Board (GMB) is the major actor in sorghum and maize marketing in both districts. Groundnut is sold to both rural and urban consumers after processing it to peanut butter locally within the production zones. Goats and cattle are mostly supplied to the Harare market by middlemen collecting these livestock from village markets and moving door-to-door to buy enough quantity to transport to Harare. Honey production and marketing is still at its initial stage through the support of HELP from Germany and the Zimbabwe Apiculture Trust projects. Long dry season is a challenge in honey production. The Pfumvudza program supported by the Presidential free input scheme helped in introducing and scaling conservation agriculture practices in Zimbabwe. Though there is strong integration of crop-livestock systems at both districts, the level of manure use is gradually decreasing because farmers receive chemical fertilizer support from the Pfumvudza program and applying manure to crop fields is labor-intensive. The input supply system is more competitive in Murehwa district where there are quite several input suppliers in town. The possible interventions that favor agroecological transitions are: (1) honey processing plants and supply of beehives to potential areas, (2) encouraging manure use in crop production, possibly linking it to the basins preparation requirement to be eligible for the presidential input subsidy scheme, (3) support the organic vegetable production initiatives and explore market segments in Harare paying premium prices for certified organic products, (4) Expedite payment systems in sorghum and maize marketing with GMB, and (5) sesame production with agroecologically friendly agronomy and improve markets.